Selective Binding of anti-DNA Antibodies to Native dsDNA Fragments of Differing Sequence - Uccellini, Melissa B. (2012)
Systemic autoimmune diseases are characterized by the development of autoantibodies directed against a limited subset of nuclear antigens, including DNA. DNA-specific B cells take up mammalian DNA through their B cell receptor, and this DNA is subsequently transported to an endosomal compartment where it can potentially engage TLR9. We have previously shown that ssDNA-specific B cells preferentially bind particular DNA sequences, and antibody specificity for short synthetic oligodeoxynucleotides (ODNs) has been shown. Since CpG-rich DNA, the ligand for TLR9 is found in low abundance in mammalian DNA, we sought to determine whether antibodies derived from DNA-reactive B cells showed binding preference for CpG-rich native dsDNA, and thereby select immunostimulatory DNA for delivery to TLR9. We examined a panel of anti-DNA antibodies for binding to CpG-rich and CpG-poor DNA fragments. We show that a number of anti-DNA antibodies do show preference for binding to certain native dsDNA fragments of differing sequence, but this does not correlate directly with the presence of CpG dinucleotides. An antibody with preference for binding to a fragment containing optimal CpG motifs was able to promote B cell proliferation to this fragment at 10-fold lower antibody concentrations than an antibody that did not selectively bind to this fragment, indicating that antibody binding preference can influence autoreactive B cell responses.